The product of the UL31 gene of herpes simplex virus 1 is a nuclear phosphoprotein which partitions with the nuclear matrix. - Chang, Y E (1993)
The nucleotide sequence of the UL31 open reading frame is predicted to encode a basic protein with a hydrophilic amino terminus and a nuclear localization signal. To identify its gene product, we constructed a viral genome in which the thymidine kinase gene was inserted between the UL31 and UL32 open reading frames. The thymidine kinase gene was then deleted, and in the process, the 5' terminus of the UL31 open reading frame was replaced with a 64-bp sequence in frame with the complete, authentic sequence of the UL31 open reading frame. The inserted sequence encoded a hydrophilic epitope derived from glycoprotein B of human cytomegalovirus and for which a monoclonal antibody is available. We report that in infected cells, the tagged protein localized in and was dispersed throughout the nucleus. Nuclear fractionation studies revealed that the UL31 protein partitions with the nuclear matrix. The protein is phosphorylated in infected cells maintained in medium containing 32Pi.